Using the Quantum Potential in Elementary Portfolio Management: Some Initial Ideas - Khaksar, Hossein; Haven, Emmanuel; Nasiri, Sina; Jafari, Gholamreza (Mdpi, 2021)
Owing to the globalization of the economy, the concept of entangled markets started to form, and this occurrence has smoothed the entrance of quantum mechanics into behavioral finance. In this manuscript, we introduce quantum risk and perform an analysis on portfolio optimization by controlling the quantum potential. We apply this method to eight major indices and construct a portfolio with a minimum quantum risk. The results show quantum risk has a power law behavior with a time-scale just as a standard deviation with different exponents.
Keywords: finance; portfolio and risk management; quantum physics